2013
DOI: 10.1177/1045389x13507349
|View full text |Cite
|
Sign up to set email alerts
|

A new imaging approach for in situ and ex situ inspections of conductive fiber–reinforced composites by magnetic induction tomography

Abstract: Fiber-reinforced plastics for industrial applications face constantly increasing demands regarding efficiency, reliability, and economy. Furthermore, it was shown that fiber-reinforced plastics with tailored reinforcements are superior to metallic or monolithic materials. However, a trustworthy description of the load-specific failure behavior and damage evolution of composite structures can hardly be given, because these processes are very complex and are still not entirely understood. Among other things, sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…As the carbon fibres in CFRPs exhibit electrical conductivity, MIT could be a potential NDE technique providing a tomographic approach to traditional eddy current testing. This was verified in [72] where damages in carbon fiber-reinforced plastics were experimentally investigated. Another 3D experimental study has also demonstrated that images of one or more hidden defects inside CFRPs can be reconstructed, although differences in defect size (15 and 25 mm diameter holes within CFRP layers) could not be distinguished [73].…”
Section: Non-destructive Evaluationmentioning
confidence: 63%
“…As the carbon fibres in CFRPs exhibit electrical conductivity, MIT could be a potential NDE technique providing a tomographic approach to traditional eddy current testing. This was verified in [72] where damages in carbon fiber-reinforced plastics were experimentally investigated. Another 3D experimental study has also demonstrated that images of one or more hidden defects inside CFRPs can be reconstructed, although differences in defect size (15 and 25 mm diameter holes within CFRP layers) could not be distinguished [73].…”
Section: Non-destructive Evaluationmentioning
confidence: 63%
“…In a typical 2D phantom study case, the cross-sectional images of the properties of the object can be reconstructed using the voltage or phase measurements collected from the inductive coils. Because of the non-hazardous, non-invasive and contactless natures of MIT, its use has been proposed for numerous applications, including foreign material monitoring [1], geological exploration [2], non-destructive evaluations [3,4,5], and biomedical imaging [6,7,8,9,10,11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Many non-destructive evaluation (NDE) techniques have been applied in this area to CFRP, including low frequency vibration [1], ultrasonic methods [2][3][4][5], radiography [6][7][8], thermography [9,10] and eddy current testing [11][12][13][14]. More recently, soft field tomography techniques have also been used for damage detection in CFRP using electrical impedance tomography (EIT) [15][16][17]; however, magnetic induction tomography (MIT)-based research in this area remains very limited [18].…”
Section: Introductionmentioning
confidence: 99%